Mathematical Model Analysis of Diabetes for Glucose-Insulin Interaction in Human Body - Akter, Sonia; Biswas, Md Haider Ali; Srinivas, M. N.; Das, Kalyan (Discontinuity, Nonlinearity, and Complexity, 2026)
This research work proposes a novel method for controlling diabetes blood glucose levels. For the research of Type 1 Diabetes, we proposed a novel mathematical model. The homeostasis related with endocrinal logical regulation of glucose and glycogen levels in the human body by the hormones insulin and glucagon is attempted to be incorporated into a therapeutically feasible mathematical model. All plasma glucose concentrations, generalized insulin, and plasma insulin concentrations are taken into consideration by the model. Steady state analysis of the model is discussed. Local stability of the proposed model has been discussed using Routh-Hurwitz criteria. Global steadiness is also discussed. The numerical solution depicts the difficult condition faced by diabetes patients. MATLAB was used to carry out computer simulations for the analytical findings. As diabetics as very sensitive disease which is highly interrelated with various elements, in this perception we carried out computer simulations of various elements (attributes) in the segment of sensitivity analysis.